Determining the Structure and In Vitro Antioxidant Activity of Sulfated Polysaccharides from Cardamine hupingshanensis. (20th October 2021) - Zhang, Zimu; Huang, Xiufang; Li, Shichan; Luo, Kai
Abstract: Plant and fungal polysaccharides have been extensively studied for their anticoagulant, antioxidant, antitumor, immunomodulatory, and hypoglycemic activities. Furthermore, the inherent bioactivities of various polysaccharides can be improved by appropriate chemical modifications that can confer novel properties. Particularly, Cardamine hupingshanensis polysaccharides (CHPs) have been reported to exhibit curative action against diabetes in a mouse model. Therefore, in this study, CHPs are extracted by the hot water extraction method and modified by sulfation using the sulfur trioxide‐pyridine method. Anion‐exchange chromatography is performed to obtain pure, sulfated CHPs (SCHP‐II). Nuclear magnetic resonance imaging and high‐performance liquid chromatography are performed to determine the structure and composition of SCHP‐II, respectively. The molecular weight of SCHP‐II is determined to be 22.2 kDa. A n in vitro antioxidation activity assay performed using 2, 2‐azino‐bis‐3‐ethylbenzthiazoline‐6‐sulfonic acid showed that SCHP‐II exhibited better free radical‐scavenging ability than CHPs. Therefore, it is concluded that SCHP‐II can be used as an antioxidant in food and medicinal products. Abstract : The C. hupingshanensis polysaccharide is modified by sulfation using pyridine sulfide trioxide. The specific structures are analyzed by NMR and in vitro antioxidant activity studies are performed. The sulfation modification could improve the antioxidant activity of C. hupingshanensis polysaccharide.